The Initial Mass Function of Stars and Brown Dwarfs in the Upper Sco Association - K. L. Luhman (The Astronomical Journal)
I present infrared spectroscopy of 37 brown dwarf candidates in the Upper Scorpius (Upper Sco) association, 35 of which are classified as young and cool, making them likely members. This sample includes many of the faintest spectroscopically confirmed members ( K = 16–17 mag), which should have masses down to ∼0.007–0.01 M _⊙ for the range of ages in Upper Sco (7–14 Myr). Using my updated membership catalog for Upper Sco, I have estimated the initial mass function (IMF) for a field in the center of the association that encompasses ∼80% of the known members. I have derived IMFs in the same manner for previous membership samples in three other star-forming populations, consisting of IC 348, Taurus, and Chameleon I. When using logarithmic mass bins, the substellar IMFs for Upper Sco and the other young regions are roughly flat down to the completeness limits of ∼0.01 M _⊙ . These IMFs are broadly similar to mass functions recently measured for the solar neighborhood. Finally, I have used W1−W2 colors to search for excess emission from circumstellar disks among the late-type objects in my new census of Upper Sco. I measure an excess fraction of 52/200 for members with spectral types of M6.25–M9.5, which is similar to results from previous membership catalogs. For the L-type members, it is difficult to detect the small W2 excess emission produced by typical disks around brown dwarfs because of the large uncertainties in spectral types, which preclude accurate estimates of the photospheric colors. Thus, W2 photometry provides poor constraints on the presence of disks for the L-type members of Upper Sco.